Evaluation of impact factors on PM2.5 based on long-term chemical components analyses in the megacity Beijing, China. (July 2016) - Chen, Yuan; Schleicher, Nina; Cen, Kuang; Liu, Xiuli; Yu, Yang; Zibat, Volker; Dietze, Volker; Fricker, Mathieu; Kaminski, Uwe; Chen, Yizhen; Chai, Fahe; Norra, Stefan
Abstract: Nine years of sampling and analyses of fine particles (PM2.5 ) were performed in Beijing from 2005 to 2013. Twenty-seven chemical elements and black carbon (BC) in PM2.5 were analyzed in order to study chemical characteristics and temporal distribution of Beijing aerosols. Principle component analysis defined different types of elemental sources, based on which, the influences of a variety of anthropogenic activities including governmental intervention measures and natural sources on air quality were evaluated. For the first time, Ga is used as a tracer element for heating activities mainly using coal in Beijing, due to its correlation with BC and coal combustion, as well as its concentration variation between the heating- and non-heating periods. The traffic restrictions effectively reduced emissions of relevant heavy metals such as As, Cd, Sn and Sb. The expected long-term effectiveness of the steel smelters relocation was not observed due to the nearby relocation with increased capacity. Firework display during every Chinese spring festival season and special events such as the Olympic Games resulted in several times higher concentrations of K, Sr and Ba than other days and thus they were proposed as tracers for firework display. The impacts of all these factors were quantified and evaluated. Sand dust or dust storms induced higher concentrations of geogenic elements in PM2.5 compared to non-dust days. Sustainable mitigation measures, such as traffic restrictions, are necessary to be continued and improved to obtain more "blue sky" days in the future. Highlights: Chemical components of aerosol particulates were analyzed in Beijing for nine years. Different sources of PM2.5 were defined by principle component analysis. The influences of mitigation measures on air quality were quantified and evaluated. For the first time, gallium (Ga) was used as a tracer for coal combustion in China.